Problemas de saúde autorreferidos por idosos e representações sociais - Rodrigues, Tatyanni Peixoto (2013)
Evidence problems related to aging involves dimensions and socio-economic policies, among them, contrasts out social security and health policies with emphasis of the health of the elderly, although one dimension and another are deeply interconnected. Regarding the health of the elderly, it s important to understand the interrelationship between this health and the aging as it is represented and experienced by the elderly constituting the center of interest of this study. Therefore this study has the objectives to know the social representations on aging and health problems for the elderly and identify self-reported by the elderly. This is a study of mixed approach (quantitative and qualitative) conducted with 714 elderly residents in the city of João Pessoa, Paraíba, Brazil. Data collection was conducted from an interview and tests of the Free Word Association with the inductive term: aging and health. Data obtained from interviews were statistically analyzed from a bivariate analysis of the data: information collected by Test Free Word Association was organized in a corpus and analyzed with the help of software Alceste: 10. The population studies is characterized in being mid-young , predominantly female, married, with a monthly income of a minimum wage, with the level of basic education and frequenter of the Health System and the elderly with incomes of minimum wage are functionally independent. The association of self-reported diseases with the Katz analysis by the chi-square test revealed that chronic obstructive pulmonary disease (COPD) was the variable of significance. Thus, it is showed that the onset of these diseases in the elderly may be related to socioeconomic, cultural and biological aspects. They represent aging and health with more negative contents which has notably influenced the adoption of health practices healthy. The results reinforce the need for special attention to the elderly population, based on the principles of the Health System, seeking comprehensive care.